IDENTIFICACIÓN Y DESCRIPCIÓN DE LAS ECTOMICORRIZAS ZONA QUEMADA Y UNA ZONA SIN ALTERAR DEL CARRASCAL DE NAZAR ( NAVARRA ) - Román, D. E.; Miguel, M. D. E. (Publicaciones de Biología, Universidad de Navarra, Serie Botánica, 2000)
Since 1998, a field study has been undertaken in a Quercus ilex L. subsp. ballota (Desf.) Samp. forest located in Nazar (Navarra, Spain). This study aims to establish a qualitative and quantitative comparison between the ectomycorrhizal morphotypes which have been collected, described and identified in a burned site and in a non- disturbed one within this forest. Thus, this study aims to contribute to the knowledge of the ectomycorrhizae associated with evergreen oak in field conditions, because most of the studies on evergreen oak ectomycorrhizae are related to truffle growing or artificial mycorrhization in the nursery.
Keywords: Ectomycorrhizae; fire; identification; morphology; Quercus ilex; Tuber melanosporum